2016
DOI: 10.1103/physrevfluids.1.032402
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between Koopman mode decomposition, resolvent mode decomposition, and invariant solutions of the Navier-Stokes equations

Abstract: The relationship between Koopman mode decomposition, resolvent mode decomposition, and exact invariant solutions of the Navier-Stokes equations is clarified. The correspondence rests upon the invariance of the system operators under symmetry operations such as spatial translation. The usual interpretation of the Koopman operator is generalized to permit combinations of such operations, in addition to translation in time. This invariance is related to the spectrum of a spatiotemporal Koopman operator, which has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…The goal of Dynamic Mode Decomposition (DMD) (Schmid 2010;Rowley et al 2009) is also to compute modes which oscillate at a distinct frequency, suggesting that resolvent analysis is attempting to approximate DMD modes from the equations instead of time-resolved data. A striking similarity between the most amplified resolvent mode and the DMD mode was noted by Gómez et al (2014) in turbulent pipe flow and the relationship between resolvent analysis and DMD was formalised in Sharma et al (2016).…”
Section: Introductionmentioning
confidence: 73%
“…The goal of Dynamic Mode Decomposition (DMD) (Schmid 2010;Rowley et al 2009) is also to compute modes which oscillate at a distinct frequency, suggesting that resolvent analysis is attempting to approximate DMD modes from the equations instead of time-resolved data. A striking similarity between the most amplified resolvent mode and the DMD mode was noted by Gómez et al (2014) in turbulent pipe flow and the relationship between resolvent analysis and DMD was formalised in Sharma et al (2016).…”
Section: Introductionmentioning
confidence: 73%
“…Effectively, then, mode structure is obtained by approximating the (action of the) resolvent operator. Sharma et al (2016) and Towne et al (2018) have noted a correspondence between resolvent modes, DMD, and spectral Proper Orthogonal Decomposition (SPOD) modes. In particular, Towne et al (2018) noted that resolvent modes are equivalent to SPOD modes when the nonlinear forcing is uncorrelated in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside DMD, other related methods have been proposed to extract Koopman modes from turbulent flows that may circumvent some of these issues. For example, Arbabi & Mezić (2017) proposed an approach based on harmonic averaging to extract Koopman modes in high-Reynolds number lid-driven cavity flow, while Sharma et al (2016) demonstrated a connection between Koopman modes and modes of the resolvent operator.…”
Section: Introductionmentioning
confidence: 99%